Soil heterogeneity in the horizontal distribution of microplastics influences productivity and species composition of plant communities - Zhang, Xiao-Mei; Cao, Xiao-Xiao; He, Lin-Xuan; Xue, Wei; Gao, Jun-Qin; Lei, Ning-Fei; Chen, Jin-Song; Yu, Fei-Hai; Li, Mai-He (Frontiers in Plant Science, 2022)
Contamination of soils by microplastics can have profound ecological impacts on terrestrial ecosystems and has received increasing attention. However, few studies have considered the impacts of soil microplastics on plant communities and none has tested the impacts of soil heterogeneity in microplastics. We grew experimental plant communities in soils with either homogeneous or heterogonous distribution of each of six common microplastics differing in chemical composition and/or morphology, i.e., polystyrene foams (EPS), polyethylene fibers (PET), polyethylene beads (HDPE), polypropylene fibers (PP), polylactic beads (PLA) and polyamide beads (PA6). Total and root biomass of the whole communities were significantly higher in the homogeneous than in the heterogeneous treatment when the microplastic was PET and PP, smaller when it was PLA, but not different when it was EPS, HDPE or PA6. In the heterogeneous treatment, total and root biomass of the communities were significantly smaller in the patches with a higher (0.2%) concentration of microplastics than in the patches without microplastics when the microplastic was EPS, but were greater when the microplastic was PET or PP. Additionally, in the heterogeneous treatment, root biomass was significantly smaller in the patches with than without microplastics when the microplastic was HDPE, and shoot biomass was also significantly smaller when the microplastic was EPS or PET. Soil heterogeneity in EPS significantly decreased community evenness and Shannon diversity index, but soil heterogeneity in PET increased community evenness. We conclude that soil heterogeneity in microplastics can influence productivity and species composition of plant communities, but such an effect varies depending on microplastic types.